Inhibition of F1 -ATPase from Trypanosoma brucei by its regulatory protein inhibitor TbIF1 - Gahura, Ondřej; Panicucci, Brian; Váchová, Hana; Walker, John E; Zíková, Alena (The FEBS journal, 2018)
Hydrolysis of ATP by the mitochondrial F-ATPase is inhibited by a protein called IF1 . In the parasitic flagellate, Trypanosoma brucei, this protein, known as TbIF1 , is expressed exclusively in the procyclic stage, where the F-ATPase is synthesizing ATP. In the bloodstream stage, where TbIF1 is absent, the F-ATPase hydrolyzes ATP made by glycolysis and compensates for the absence of a proton pumping respiratory chain by translocating protons into the intermembrane space, thereby maintaining the essential mitochondrial membrane potential. We have defined regions and amino acid residues of TbIF1 that are required for its inhibitory activity by analyzing the binding of several modified recombinant inhibitors to F1 -ATPase isolated from the procyclic stage of T. brucei. Kinetic measurements revealed that the C-terminal portion of TbIF1 facilitates homodimerization, but it is not required for the inhibitory activity, similar to the bovine and yeast orthologs. However, in contrast to bovine IF1 , the inhibitory capacity of the C-terminally truncated TbIF1 diminishes with decreasing pH, similar to full length TbIF1 . This effect does not involve the dimerization of active dimers to form inactive tetramers. Over a wide pH range, the full length and C-terminally truncated TbIF1 form dimers and monomers, respectively. TbIF1 has no effect on bovine F1 -ATPase, and this difference in the mechanism of regulation of the F-ATPase between the host and the parasite could be exploited in the design of drugs to combat human and animal African trypanosomiases.
Keywords: mutace; Cattle; Animals; skot; sekvenční homologie; Proton-Translocating ATPases; sekvence aminokyselin; Enzyme Inhibitors; protonové ATPasy; Mutation; Amino Acid Sequence; Proteins; Sequence Homology; regulace genové exprese; proteiny; Trypanosoma brucei brucei; inhibitory enzymů; Gene Expression Regulation; zvířata